Sevelamer Carbonate Crystal-Induced Colitis - T. Lai; A. Frugoli; B. Barrows; M. Salehpour (Case Reports in Gastrointestinal Medicine)
Hyperphosphatemia is a common and well-described complication of end-stage renal disease. Despite strict dietary constraints and compliance, phosphate binders such as calcium acetate and/or sevelamer carbonate are also needed to treat secondary hyperparathyroidism. This case vignette describes an underrecognized adverse effect of a phosphate binder, sevelamer carbonate, inducing colitis in a 47-year-old male with insulin-dependent diabetes complicated by end-stage renal disease. He presented for recurrent abdominal pain with associated nausea and was found to have multiple circumferential lesions on computed tomography including distal ascending, transverse, and proximal descending colon. Colonoscopy demonstrated nearly obstructing lesions worrisome for colonic ischemia or inflammatory bowel disease. Pathological review of histology demonstrated ragged colonic mucosa with ulcerative debris and nonpolarizing crystalline material at the sites of ulceration, morphologically consistent with the phosphate binder, sevelamer carbonate. Sevelamer carbonate was discontinued, and the patient was transitioned to calcium carbonate with strict dietary restrictions. His symptoms improved with the cessation of sevelamer, and he was subsequently discharged home. He eventually underwent renal transplant without redevelopment of symptoms. Recognition of this underreported complication of sevelamer carbonate, phosphate binder, is of utmost importance in directing appropriate therapy with cessation of this medication in the setting of gastrointestinal complaints or more specifically enteritis and colitis. Clinicians providing care to end-stage renal patients taking either sevelamer and/or sodium polystyrene sulfonate should have increased awareness of the possible gastrointestinal side effects.